Correction to: The quality of primary care provided to the elderly in Israel - Rachel Podell; Vered Kaufman-Shriqui; Yael Wolff Sagy; Orly Manor; Arie Ben-Yehuda (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.